A Comprehensive Analysis Of Mppt Techniques For Photovoltaic Systems Under Partial Shading Conditions (Texas Journal of Engineering and Technology, 2025)
Maximizing power extraction from photovoltaic (PV) systems is crucial for improving efficiency, particularly under partial shading conditions (PSCs). The high cost and relatively low conversion efficiency of PV panels necessitate effective maximum power point tracking (MPPT) techniques to ensure operation at the maximum power point (MPP). This paper presents a comprehensive review of 11 MPPT methods reported in the literature, alongside recent advancements in hardware design methodologies. The MPPT techniques are classified into three categories—Classical, Intelligent, and Optimization-based—according to their underlying tracking algorithms. Under uniform irradiance, classical methods are generally preferred due to the presence of a single peak in the power–voltage (P–V) curve. However, under PSCs, the P–V curve exhibits multiple peaks, including one global MPP (GMPP) and several local MPPs (LMPPs). As a result, intelligent and optimization-based techniques have emerged to accurately identify the GMPP among all local peaks. Each MPPT technique is critically analyzed in terms of sensor requirements, hardware implementation complexity, performance under PSCs, cost, tracking speed, and tracking efficiency. This study consolidates recent advancements and highlights potential research directions to support further development in the field.